2011
DOI: 10.1200/jco.2010.34.0778
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Breast Cancer in Women With a CHEK2 Mutation With and Without a Family History of Breast Cancer

Abstract: CHEK2 mutation screening detects a clinically meaningful risk of breast cancer and should be considered in all women with a family history of breast cancer. Women with a truncating mutation in CHEK2 and a positive family history of breast cancer have a lifetime risk of breast cancer of greater than 25% and are candidates for magnetic resonance imaging screening and for tamoxifen chemoprevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
168
4
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(185 citation statements)
references
References 37 publications
6
168
4
7
Order By: Relevance
“…Thus, the breast cancer risk estimates for c.1100delC mutation carriers are influenced by family history. The lifetime risk of breast cancer for carriers of CHEK2 truncating mutations is estimated to range from 20% for a woman with no affected relative to 44% for a woman with a first-and a second-degree relative affected (27). Interestingly, the CHEK2 missense-mutation I157T is a lower-risk allele with approximately 1.5-fold elevated cancer risk among unselected and familial cases, whereas it associates specifically with approximately fourfold increased risk of lobular breast cancer (28).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the breast cancer risk estimates for c.1100delC mutation carriers are influenced by family history. The lifetime risk of breast cancer for carriers of CHEK2 truncating mutations is estimated to range from 20% for a woman with no affected relative to 44% for a woman with a first-and a second-degree relative affected (27). Interestingly, the CHEK2 missense-mutation I157T is a lower-risk allele with approximately 1.5-fold elevated cancer risk among unselected and familial cases, whereas it associates specifically with approximately fourfold increased risk of lobular breast cancer (28).…”
Section: Discussionmentioning
confidence: 99%
“…Sanger sequencing identified 619 variants within the targeted region, of which eight were a common 16 base insertion not expected to be detected by NGS [13]. Of the remaining 611 Sanger identified variants; there were no false negatives within our data set, resulting in 100% sensitivity.…”
Section: Analytical Sensitivitymentioning
confidence: 92%
“…Another clinically normal sample harbored a c.1100delC variant in CHEK2. Mutations in this gene are known to be of lower penetrance, increasing a patient's risk of breast cancer or Li-Fraumeni like syndrome, but at a lower penetrance where it's not entirely unusual that we could find a mutation in a normal donor sample [3,13].…”
Section: Accuracymentioning
confidence: 97%
“…Raised expression of a number of genes due to single nucleotide polymorphisms (SNPs) increases the breast cancer incidence risk [4,5]. Many researchers have demonstrated that genetic polymorphisms are one of the reasons for the individual difference in the incidence of cancer [6].…”
Section: Introductionmentioning
confidence: 99%